Simulasi Sisa Klor pada Jaringan Distribusi Wilayah Utara Perumda Air Minum Kota Padang - Puti Sri Komala; Nadia Tripermata Dewi; Ashifa Adetya (Fakultas Teknik, 2023)
AbstractResidual chlorine levels in water need to be maintained in the distribution network to prevent the presence of pathogens in drinking water that can be consumed by humans. According to Minister of Health Regulation No. 736/Menkes/PER/VI/2010 concerning Procedures for Monitoring the Quality of Drinking Water is in the range of 0.2 – 1.0 mg/l. This simulation was carried out to analyze the presence of residual free chlorine in the PDAM Padang, North Region distribution network sourced from the IPA Palukahan using EPANET software. Analysis of chlorine decay to determine the coefficient of bulk reaction and wall reaction was carried out at the Palukahan Reservoir outlet pipe for 6 hours using the DPD method. The dose of adding chlorine to the reservoir is 2.20 mg/l. The residual chlorine simulation results obtained a Global Bulk Reaction value of -0.105 and a Global Wall Coefficient value between -0.1 to -0.5 ranging from 0.12 mg/l – 2.20 mg/l. Low residual chlorine i.e., 1 mg/L, is located at a distance of 10-12 km from the reservoir, while high residual chlorine value, namely 1 mg/L, is located at 1-5 km from the reservoir. The results of this simulation show that chlorine levels in some distribution pipeline networks did not meet the drinking water regulation. The simulation results show that the dose and pipe spacing affect the remaining chlorine received by the customer.Keywords: disinfectant, distribution network, Padang City Water Supply Corporation (PDAM), remaining chlor, EPANET simulation